Feasibility of Using the Expression of the Retinoblastoma Gene as a Marker for Assessing the Embryogenic Potential of Coconut Ovary Culture - P. I. P. Perera; V. Hocher; L. K. Weerakoon; D. M. D. Yakandawala; J. L. Verdeil (International Coconut Community, 2009)
Coconut is a monocotyledonous tree crop that is highly recalcitrant to in vitro culture conditions. Ovary culture is a promising technique for clonal propagation of coconut. A greater understanding of the fundamental aspects of somatic embryogenesis and plant regeneration is very important in achieving a break-through. Identification of tissues having a high embryogenic potential at an early stage is also very important to achieve a high regeneration efficiency and to avoid maintenance of non-responsive cultures for a prolonged period. In situ hybridization was employed to study the expression of CnRb gene in selected tissues, to identify a potential molecular marker to assess the embryogenic potential of coconut ovary cultures. The results revealed that in situ hybridization can be used to detect the expression of CnRb gene in the cells. It was possible to establish a relationship between the meristematic activity and expression of CnRb gene in the tissues tested. CnRb mRNAs were mainly localized in the meristematic cells and tissues such as calli and growing point of the developing shoots.